PENYELESAIAN SENGKETA KONSUMEN MELALUI MEDIASI OLEH BADAN PENYELESAIAN SENGKETA KONSUMEN (BPSK) KOTA PARIAMAN - Gusmawati, Neli; Mashudi, Mashudi; Oktarina, Neneng (Ensiklopedia Sosial Review, 2019)
In the era of globalization the development of society in the economic and business sectors is growing very rapidly. These highly dynamic economic and business developments turned out to have quite fundamental implications for the shift in legal institutions and institutions in Indonesia. The implications for legal institutions are caused by inadequate norms to support economic and business activities that are developing so rapidly including developments in dispute resolution efforts that arise in the business world, one of which is about consumer disputes. The dynamism of economic and business development also needs to be balanced with regulations in the field of law. This research is an analytical descriptive research. From the research results it can be explained that: The implementation of mediation in the settlement of consumer disputes at the City Consumer Dispute Settlement Agency is carried out through the role of three mediators from the three assembly elements present at BPSK, namely government elements, business actors and consumer elements. The mediation carried out at the Padang City BPSK always exceeds the mandatory timeframe, so that the time is inadequate in the success of the mediation, the mediation seems to be forced upon the parties because the BPSK assembly believes the mediation decision can equalize the position of consumers who were previously in a weak position. The legal consequences of the implementation of mediation in the settlement of consumer disputes by BPSK Kota Pariaman can be in the form of agreement or disagreement of the parties as outlined in a determination, and the determination is also not infrequently deviated due to the absence of an executive power over the BPSK Kota Pariaman determination or decision.